A generalized anisotropic damage interface model for finite strains - Spannraft, Lucie; Steinmann, Paul; Mergheim, Julia (Journal of the Mechanics and Physics of Solids, 2023)
This contribution presents a generalized mechanical interface model for nonlinear kinematics. The interface's response is non-coherent, i.e. allows for a jump in the deformations and for cohesive failure, and also includes interfacial (in)elasticity, which means that an additional membrane stiffness is introduced in the interface. This can result in a jump in the tractions across the interface and induces membrane stresses for in-plane stretches. An anisotropic cohesive law, i.e. dependent on the spatial interface normal, is formulated which induces for nonlinear kinematics additional shear-like stresses within the interface to satisfy the balance of angular momentum. The cohesive and membrane degradations are coupled via damage variables of the different deformation modes to account for an interaction. It is shown that the model is thermodynamically consistent, fulfills the balance equations and material frame indifference. An interface element with the generalized interface model is implemented as a user element in ABAQUS. Numerical examples illustrate the influence of damage coupling on the mechanical response of adhesive layers.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Anisotropic cohesive zone; Anisotropic material; Damage; Delamination; Finite elements; Finite strain; Generalized interface; Interface (in)elasticity

Generalized interfaces enabling macroscopic modeling of structural adhesives and their failure - Spannraft, Lucie; Possart, Gunnar; Steinmann, Paul; Mergheim, Julia (Forces in Mechanics, 2022)
This contribution presents a geometrically linear and thermodynamically consistent model for generalized mechanical interfaces. The interface's response is kinematically non-coherent, i.e. allows for a displacement jump and for anisotropic cohesive failure, and kinetically non-coherent, i.e. allows for traction jumps across the interface and membrane damage. The traction jump ensues from an interfacial (in)elasticity formulation which introduces additional membrane stiffness and membrane stresses under in-plane stretch in the interface. The cohesive and membrane degradations are coupled via damage variables determined by the different deformation modes to account for their interaction. A numerical example applies the presented model to brittle interfaces adhesively bonding two substrates. By subjecting the interface to a small in-plane stretch prior to performing a peel test, the influence of damage coupling on the mechanical response is illustrated.
Created from Fastlane, Scopus look-up
Keywords: Anisotropic cohesive zone; Damage; Generalized interfaces; Interface (in)elasticity; Structural adhesives

Grain boundary interaction based on gradient crystal inelasticity and decohesion - Spannraft, Lucie; Ekh, Magnus; Larsson, Fredrik; Runesson, Kenneth; Steinmann, Paul (Computational Materials Science, 2020)
This paper presents a model for geometrically non-coherent grain boundary interaction premised on gradient-extended crystal inelasticity. The appropriate kinematics, the constitutive relations and the balance equations are established for a polycrystal including grain interaction. More specifically, this contribution proposes a coupling of the microtraction and grain boundary decoheion, which is represented as damage. As a consequence, decohesion exerts an impact on the standard tractions as well as on the microtractions along the grain boundaries. The appropriate modeling framework is assessed in terms of numerical results for a bicrystal that is subjected to simple shear. A comparison with the situation without such coupling effect shows that the microtractions along the grain boundary reduce for increasing damage and a microfree boundary is approached when the damage approaches unity.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Boundary conditions; Decohesion; Gradient crystal plasticity; Grain boundary interaction

Implementation of generalized mechanical interfaces - Spannraft, Lucie; Mergheim, Julia; Steinmann, Paul (Proceedings in Applied Mathematics and Mechanics, 2019)
For an accurate approximation of the mechanical behavior of interfaces undergoing tension, shear and in‐plane stretch deformation, the definition of an appropriate interface constitutive model is crucial. Distinct interface models, such as cohesive zone models are well investigated. However, only little research considering energetic interface models, especially inelastic models, and generalized mechanical interfaces is conducted. Although multiple possibilities to apply cohesive zone models in commercial software exist, to the authors' knowledge, the material properties provided are generally limited by basic cohesive laws and any definition of energetic interface models lacks. In order to benefit from the advantages of commercial FE software, a generalized mechanical interface model is implemented in ABAQUS. The employed constitutive model combines a cohesive zone model with an energetic interface model.<br